Epithermal neutron activation dosimetry–(n, γ) reactions under boron-based filters - Vladimir Radulović; Nicolas Thiollay; Hubert Carcreff; Anže Pungerčič; Klemen Ambrožič; Christophe Destouches; Andrej Trkov (Scientific Reports)
Abstract Neutron activation dosimetry is the primary method for the determination of the neutron flux or fluence, and in general, it is sensitive to the thermal and resonance energy ranges (radiative capture reactions– $$(n,γ )$$ ( n , γ ) reactions) and the fast energy range (threshold reactions). However, there are very few nuclear reactions which are sensitive specifically to neutrons in the intermediate–epithermal–energy region. This energy region, along with the fast energy range, will become particularly important in the development and deployment of new reactor technologies (Generation IV reactors and Small Modular Reactors–SMRs), which are currently being championed as technologies enabling a meaningful contribution to decarbonization and the fight against climate change, as well as nuclear fusion. The epithermal neutron energy range is also of particular importance for Boron Neutron Capture Therapy (BNCT), a neutron-based cancer therapy, particularly effective for the treatment of head and neck cancer, malignant meningioma, melanoma and hepatocellular carcinoma. This work investigates and demonstrates the applicability of a particular set of $$(n,γ )$$ ( n , γ ) reactions in conjunction with boron-based neutron filters to achieve sensitivity in the epithermal energy region, and discusses avenues for future research in this context.